On a mathematical model of the dysfunctions in smooth pursuit eye tracking - Pavankumar, C V (Journal of Experimental Sciences, 2012)
A simple mathematical deterministic model of dysfunctions of eye- tracking is presented in this paper. The model is formulated as a second order nonlinear ordinary differential equation, incorporating non Hookesien cubic restoring force. Perturbation technique with the nonlinear restoring force coefficient as the perturbation parameter is employed for solving the basic nonlinear equation. Numerical estimation of the angular displacement and angular velocity is computed for a wide spectrum of the eye dysfunction. The significance of the effects of the time, frequency and amplitude of the exiting force on angular displacement and angular velocity has been discussed by adopting ANOVA technique. The table shows the critical levels of time (τ), amplitude (Γ) and frequency (Î©) have also been noted corresponding to 0.05 level of significance.